Comportamento enxameatório de abelhas africanizadas (apis mellifera l.) em zona urbana de Mossoró-RN, região semiárida do nordeste brasileiro - Santos, Ricardo Gonçalves Santos (2020)
It Africanized honey bees (Apis mellifera L.) have high swarming behavior and high adaptability, characteristics that allowed the rapid propagation of these bees in tropical conditions. However, africanized honey bees have been causing problems in Brazilian cities due to the high risk of accidents that they can cause to people and animals, because they have a strong defensive instinct. This work was carried out on the Federal University of the Semi-Arid Region. The main objective of this research was to evaluate the characteristics of feral swarms of africanized honey bees in Mossoró city, in order to gain a better comprehension of the biology of these bees in urban áreas, understanding the possible factors involved in the nesting and swarming process in cities in the semiarid region of Northeast Brazil. For this, through a partnership between UFERSA and the Fire Brigade of Mossoró, 487 swarms were notified from requests made by the local community during the period from april 2015 to march 2018. In each notification of the presence of bees, various information about the swarms was recorded as: date, address, height and structure of the place where the bees were found, presence or not of nesting, position of the combs, estimate of the number of bees in the swarm, defensiveness of bees, presence of queen, queen cells, drones and combs with drone cells. Data on rainfall, air temperature, relative humidity, solar radiation and wind speed were obtained in order to evaluate the effect of climatic variables on swarming and reproductive aspects of swarms. The results showed that in urban areas of the northeastern semiarid region the swarms invest in reproduction and swarming throughout the year, however, the breeding of queens and drones is intensified in the rainy season, while the swarming peak occurs between the end of the rainy season and beginning of the dry season, which is between the months of april and september. Natural production of queen and drones in the colonies was negatively affected in periods of higher temperature, solar radiation and wind speed. There was a greater predominance of established colonies than temporary bee clusters. Honey bees showed preference for site less than 4 meters high and also prioritized the construction of their combs oriented towards the east/west direction. The lowest frequency of swarms occurs between october and march. There was no difference in the frequency of swarms between the rainy and dry periods. In Mossoró, swarms generally have a population less than 20 thousand bees and with low defensive behavior. We conclude that the natural production of queens and drones in the colonies are influenced by the environmental conditions of the Brazilian Semiarid region and that the africanized honey bees perform the peak of reproductive swarming in urban areas during the period of the year when there is greater availability of flowers in the region and when the average of environmental temperature is mild. This leds us to believe that there is a behavioral adjustment of A. mellifera to the climatic conditions of the region, avoiding the adverse conditions of the local climate. In addition, we found that, despite being generalists, the africanized honey bees are more demanding when looking for a nesting site, rather tan a temporary place for landing and resting only. On the other hand, the bees choose heights that protect them from the strongest winds, but without leaving them vulnerable to the action of natural enemies. We also conclude that the small swarms of africanized honey bees (less than 20 thousand bees) are little defensive and that this low defensiveness is also due to the proper management of swarms (use of beekeeper protection clothing and tolls, smoker), which facilitates to catch bees in areas with populous urban locations, making it possible to capture bees more safely in urban áreas